Servitude et dépendance spirituelle du chrétien dans les oeuvres catholiques de Tertullien - Davier, Fabien (Gerión. Revista de Historia Antigua, 2012)
Tertullian, first latin Father of the church, occupied an important place in the construction of the primitive church. The content of this article proposes to analyse, though Tertullian’s catholic works (193- 208), the beginning of a standardisation and regulation of the Christian faith. The whole thing is built around a lexical and contextual survey of the formalization of this Africa polemist’s thought, at a time when christianism adopted institutional and framing foundings. Resorting to vocabulary belonging to the field of slavery and dependence is away to underline the relationships of active dependence of the Christian towards God and towards their community.